Gastrointestinal Headache; a Narrative Review - Noghani, Majid; Rezaeizadeh, Hossein; Fazljoo, Sayed Mohammad Baqer; Yousefifard, Mahmoud; Keshavarz, Mansoor (Archives of Academic Emergency Medicine, 2018)
There are studies reporting primary headaches to be associated with gastrointestinal disorders, and some report resolution of headache following the treatment of the associated gastrointestinal disorder. Headache disorders are classified by The International Headache Society as primary or secondary; however, among the secondary headaches, those attributed to gastrointestinal disorders are not appreciated. Therefore, we aimed to review the literature to provide evidence for headaches, which originate from the gastrointestinal system. Gastrointestinal disorders that are reported to be associated with primary headaches include dyspepsia, gastro esophageal reflux disease (GERD), constipation, functional abdominal pain, inflammatory bowel syndrome (IBS), inflammatory bowel disorders (IBD), celiac disease, and helicobacter pylori (H. Pylori) infection. Some studies have demonstrated remission or improvement of headache following the treatment of the accompanying gastrointestinal disorders. Hypotheses explaining this association are considered to be central sensitization and parasympathetic referred pain, serotonin pathways, autonomic nervous system dysfunction, systemic vasculopathy, and food allergy. Traditional Persian physicians, namely Ebn-e-Sina (Avicenna) and Râzi (Rhazes) believed in a type of headache originating from disorders of the stomach and named it as an individual entity, the "Participatory Headache of Gastric Origin". We suggest providing a unique diagnostic entity for headaches coexisting with any gastrointestinal abnormality that are improved or cured along with the treatment of the gastrointestinal disorder.